2011
DOI: 10.18227/1982-8470ragro.v5i1.463
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de goiabas ‘Pedro Sato’ minimamente processadas e irradiadas

Abstract: Resumo -O objetivo desse trabalho foi avaliar o efeito da irradiação gama associada à atmosfera modificada passiva na conservação refrigerada de goiabas 'Pedro Sato' minimamente processadas. Foram utilizadas goiabas provenientes da região de Vista Alegre do Alto/São Paulo/Brasil. Após a colheita, as goiabas foram imediatamente transportadas ao Laboratório de Frutas e Hortaliças, pertencente ao Departamento de Gestão e Tecnologia Agroindustrial, da Faculdade de Ciências Agronômicas -UNESP -Campus de Botucatu/SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Similar to E. cibrata, camu-camu fruits (M. dubia) suffered rapid loss of firmness during storage due to the activity of enzymes pectinamethylesterase and polygalacturonase (PINTO et al, 2013). The firmness values observed are close to those found for Guava (P. guajava), since in the maturation stage considered suitable for harvest, Campos et al (2011) found firmness of 15.5 N, while E. cibrata presented firmness of 12.18 N. the comparison of maturation stages with fruits ripened on the plant was not carried out, since they did not allow more readings and were extremely softened at two days of storage. Cavalini et al (2015) found that guava cv 'Paluma' harvested on the last maturation stage only remained preserved for one day, similar to what occurred to the fruit under study.…”
Section: G a S Diniz Et Alsupporting
confidence: 76%
“…Similar to E. cibrata, camu-camu fruits (M. dubia) suffered rapid loss of firmness during storage due to the activity of enzymes pectinamethylesterase and polygalacturonase (PINTO et al, 2013). The firmness values observed are close to those found for Guava (P. guajava), since in the maturation stage considered suitable for harvest, Campos et al (2011) found firmness of 15.5 N, while E. cibrata presented firmness of 12.18 N. the comparison of maturation stages with fruits ripened on the plant was not carried out, since they did not allow more readings and were extremely softened at two days of storage. Cavalini et al (2015) found that guava cv 'Paluma' harvested on the last maturation stage only remained preserved for one day, similar to what occurred to the fruit under study.…”
Section: G a S Diniz Et Alsupporting
confidence: 76%